Psikometrika Instrumen Konsep Diri dalam Pembelajaran Matematika - Khoirunnisa, Mustika; Rahayu, Wardani; Hidajat, Flavia Aurelia (Universitas Muria Kudus, 2025)
The purpose of this study was to develop a non-test instrument that can be used to measure students' self-concept in mathematics learning. The instrument created was a self-concept questionnaire with 12 statements with three dimensions of self-concept, namely knowledge, expectations, and assessments. This instrument is in the form of a rating scale with 4 choices, namely strongly disagree, disagree, agree, and strongly agree. The respondents in this study were 306 high school students. Data processing in this study used the Rasch Model which was operated through the Winstep application. The reliability of the self-concept development instrument is in the good category with a Cronbach Alpha (KR-20) Person Raw Score value of 0.71, meaning that the development instrument in this study can be used to express students' self-concept in mathematics learning. Include from 12 items of student self-concept statements in mathematics learning valid because they meet at least one validity criterion.